DIRECTORATE GENERAL OF TAXES E-CONFERENCE INFORMATION SYSTEM FACE MATCH MODEL WITH AGILE SDLC METHOD - Lusita, Melani Dewi; Mirza, Anis; Falawi, Ardiansyah A.R. (Journal of Information System, Informatics and Computing, 2023)
After the Covid-19 pandemic, offline activities began to take place again on a massive scale. At the Directorate of Information and Communication Technology, the Directorate General of Taxes, face-to-face activities, including meetings, have started to take place again. In meeting activities, problems often occur in the management and management of meetings, such as schedule discrepancies, inadequate participant attendance lists, and less than optimal monitoring of meeting activities. To overcome this problem, an information system is needed to assist the management and administration of meetings as well as monitoring of meetings by Administrative Subdivision staff. The Meeting Management and Monitoring Information System (e-Conference) is a web-based information system that consists of two applications, namely a frontend that uses the ReactJS library and a backend that uses the ExpressJS framework with the Agile Systems Development Life Cycle (SDLC) method with the Scrum development method. The modules in this system include the login module, meeting dashboard module, meeting room module, consumption module, equipment module, meeting materials module, attendance module and management module. In the attendance module there is a face match feature with TensorFlowjs technology which is used to validate the attendance of meeting participants who are DJP employees.